Analisis Hukum Ketenagakerjaan: Perlindungan Hak-Hak Pekerja Di Indonesia - Muhammad Aldri; Rizki Sahru Ramadan; Yolanda Junia Putri; Holijah . (CV. ITTC INDONESIA, 2026)
This research is motivated by the persistent gap between regulation and implementation in protecting workers' rights in Indonesia. The main issue examined is the effectiveness of labor law in protecting workers amidst the dynamic changes in the world of work, including the emergence of informal and digital workers. This research uses a library research method with a descriptive qualitative approach, through the collection and analysis of various literature such as scientific journals, books, and relevant laws and regulations. The results show that although labor regulations have comprehensively regulated worker protection, their implementation still faces various obstacles, such as weak supervision, low company compliance, and minimal worker legal literacy. Furthermore, technological developments and globalization demand regulatory updates that are more adaptive and inclusive. The conclusion of this study emphasizes the need for strengthened supervision, increased legal education, and labor policy reform to create a fairer, more humane, and more sustainable system.